A RETROSPECTIVE FOLLOW-UP STUDY TO SHOW THE EFFECTIVENESS OF BOOSTER DOSE OF FOAM SCLEROTHERAPY SESSION AT 3RD AND 6TH MONTHS IN PREVENTING THE RECURRENCE OF VARICOSE VEINS - Farid Ullah Khan; Nauman Imtiaz Khan; Muhammad Irfan Khan; Ghazala Huma Khan; Khan, Uzair Ahmad; Tahir Iqbal Mirza (Journal of Ayub Medical College Abbottabad, 2023)
Background: Injection sclerotherapy administration is known to cause a decreased recurrence of varicose vein disease. This research aimed to investigate the recurrence of varicose vein disease after giving booster doses of injection sclerotherapy. The booster doses were given at 3rd and 6th months. Methods: 150 patients participated and all patients included ages were 30-70 in the category of ’˜low risk’ patients. The patients were both males and females. Patients participating in the study were counselled appropriately and written consent was taken from them. Moreover, the patients selected were volunteers and agreed to be part of the study. Patients who were above 70 years of age, those who were at a high-risk due to some co-morbidities (high-risk patients), patients not willing for being part of the study, those allergic to drugs being used including sclerosant and people with any known psychiatric illness or cardiac arrhythmias, deep venous thrombosis patients, patients having arteriovenous malformation/venous ulcers were all excluded. If the patient was pregnant, the gynaecology team was taken on board and the procedure was carried out. Every procedure was carried out under the direct supervision of the supervisor. Booster dose sessions of Foam Sclerotherapy were held at 3rd and 6th months of the study time. Their effectiveness was clearly observed and documentation was carried out. Results: Since it was a procedure that could be done in the OPD, there was no need for specialized anaesthesia care. It is of significant notice that when a patient of varicose veins was given a booster intravenous sclerosant injection at 3rd and 6th month of treatment, chances of recurrence decreased to 50%.